Sistem Pendukung Keputusan untuk Subsidi Biaya Perbaikan Kerusakan Kontainer Menggunakan Naive Bayes - Agung Prakesakwa; Adhe Suryani; Rendra Gustriansyah (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2019)
During the process of using containers by the importer, the shipping company as the owner of the container is often faced with the problem of those who must be responsible for handling containers that are damaged when shipping goods. This study examines the application of the Naïve Bayes method to help the container owner to make a decision in analyzing each case of objection from the importer. The analysis was carried out for each objection case submitted by the importer regarding subsidizing the cost of repairs to be given a FREE or PAID decision by considering 4 factors, which are the damaging side, the damage, the type of damage, and the cost of repairs. From 48 datasets collected and analyzed, the decision has an accuracy rate of 63.3% in subsidizing of container repair costs.